2015
DOI: 10.1111/plb.12306
|View full text |Cite
|
Sign up to set email alerts
|

Annual dormancy cycles in buried seeds of shrub species: germination ecology of Sideritis serrata (Labiatae)

Abstract: The germination ecology of Sideritis serrata was investigated in order to improve ex-situ propagation techniques and management of their habitat. Specifically, we analysed: (i) influence of temperature, light conditions and seed age on germination patterns; (ii) phenology of germination; (iii) germinative response of buried seeds to seasonal temperature changes; (iv) temperature requirements for induction and breaking of secondary dormancy; (v) ability to form persistent soil seed banks; and (vi) seed bank dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…This mechanism prevents germination from occurring under unfavourable periods for seedling establishment, enhancing survival of plant populations, especially in annual species (Schütz ; Copete et al . ). Thus, seed dormancy cycles are an important strategy in species inhabiting seasonal environments, where favourable conditions for germination and seedling survival are restricted to certain times of the year (Baskin & Baskin ).…”
Section: Introductionmentioning
confidence: 97%
“…This mechanism prevents germination from occurring under unfavourable periods for seedling establishment, enhancing survival of plant populations, especially in annual species (Schütz ; Copete et al . ). Thus, seed dormancy cycles are an important strategy in species inhabiting seasonal environments, where favourable conditions for germination and seedling survival are restricted to certain times of the year (Baskin & Baskin ).…”
Section: Introductionmentioning
confidence: 97%
“…However, Huang et al (2016) did not explore the dormancy alleviation/cycling process (i.e., the change of dormancy state) during after-ripening, which is an important life history trait in this desert annual community (Adondakis and Venable 2004). Dormancy cycling has been suggested as an important adaptation to specific habitats (Baskin and Baskin 1985, Baskin et al 1993, Finch-Savage and Footitt 2017, and is found in diverse plant forms in addition to annual plants (e.g., Cao et al 2014, Copete et al 2015. Huang et al (2016) reported only on seeds that had been after-ripened for 4-5.5 months and therefore had largely lost the primary dormancy present in freshly matured seeds.…”
Section: Introductionmentioning
confidence: 99%
“…También son inducidas a latencia secundaria por bajas temperaturas semillas hidratadas de especies de matorral como Sideritis serrata Lag. (Copete et al 2015) y de varios geófitos con latencia morfofisiológica simple y profunda del epicótilo, como ocurre en Narcissus hispanicus Gouan (Copete et al 2011), N. eugeniae Fern. Casas (Copete et al 2014) y N. radinganorum Fern.…”
Section: Discusión Y Conclusionesunclassified